PENGARUH PENAMBAHAN TEPUNG KULIT PISANG KEPOK TERHADAP KANDUNGAN GIZI, SERAT PANGAN, DAN ORGANOLEPTIK BAKSO IKAN LELE SEBAGAI UPAYA PENCEGAHAN OBESITAS - Woro Nimas Gusti Nugraheni (2022)
The prevalence of obesity at adult >18 years has increased significantly, from 14.8% in 2013 to 21.8% in 2018. Obesity can be prevented and treated, one of which is by consuming high-fiber foods. The purpose of this study was to utilize kepok banana peel flour as an alternative high-fiber food and to determine the effect of adding kepok banana peel flour in the manufacture of catfish meatballs on nutritional content, dietary fiber, and organoleptic catfish meatballs. The study used a Complete Randomized Design (RAL) consisting of three treatments and two repetitions, namely F1 (20%), F2 (25%), and F3 (30%). Organoleptic test data analysis used Kruskall Wallis test and ANOVA test. The results of the organoleptic test had a significant effect (P<0.05) on the level of preference for the texture of the meatballs. Analysis of chemical properties used the Mann Whitney and Duncan test, showed a significant effect (P <0.05) on water, protein, and carbohydrate content, but did not significantly affect the fiber content of meatballs. Meatball F2 is the best formulation with a serving nutrient composition (75 grams); energy 103.5 kcal, protein 6.8 g, fat 2.7 g, carbohydrates 14.5 g, and dietary fiber 7.3 g. These Catfish meatballs with high dietary fiber content can be used as a snack for obese and non-obese groups.